Título Padrão - CASTELLO, HUGO P. (Arquivos de Ciências do Mar, 2018)
The "chucho" or southern eagle ray, Myliobatis goodei (Garman), ranges from North Carolina in the northwestern Atlantic Ocean to Central America, and from Rio de Janeiro to Buenos Aires Province in Argentina (Bigelow & Schroeder, 1953 ; F. Schwartz, personal communication).